Revisiting the servitization-sustainability link: A case study in the professional printing supply chain - Nizar Abdelkafi; Margherita Pero; Antonio Masi; Isabella Capurso (Cleaner Logistics and Supply Chain)
This paper investigates the link between servitization and sustainability. Extant literature assumes a positive effect of servitization on sustainability, while limited contributions report that, under certain conditions, servitization can also have negative effects. Through a case study on the professional printer supply chain, we show that the positive relationship between servitization and sustainability does not always hold true, and we clarify the nature of the links between servitization and sustainability. By drawing on causal loop diagrams based on system dynamics modeling, we differentiate between “built-in sustainability in servitization” and “sustainability potential in servitization”. With the former, we refer to the inherent sustainability effect that results from the mere application of servitization. For example, servitization leads, ceteris paribus, to the reduction of the number of required printers to achieve the printing jobs required by customers. The latter shows, however, that there is a latent sustainability potential that can be released, only if refurbishing and component recycling activities take place to extend the product lifetime. The case study also highlights that a systemic view is essential for assuring the overall positive impact of servitization on the environment. If manufacturing firms or institutions cannot track the way printers are disposed, e.g., outside of the borders of a country, the full potential of sustainability embedded in servitization cannot be achieved.